2009
DOI: 10.1039/b900325h
|View full text |Cite
|
Sign up to set email alerts
|

A DNA nanoswitch incorporating the fluorescent base analogue 2-aminopurine detects single nucleotide mismatches in unlabelled targets

Abstract: DNA nanoswitches can be designed to detect unlabelled nucleic acid targets and have been shown to discriminate between targets which differ in the identity of only one base. This paper demonstrates that the fluorescent base analogue 2-aminopurine (AP) can be used to discriminate between nanoswitches with and without targets and to discriminate between matched and mismatched targets. In particular, we have used both steady-state and time-resolved fluorescence spectroscopy to determine differences in AP environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…use the fluorescence decay of 2AP positioned at the branchpoint to probe the conformation (switch state) and to detect structural differences arising from hybridization of matched and mis-matched targets (Campbell et al . 2009). The decay parameters reported enhanced base-stacking at the branchpoint on switch closure and could resolve variations in switch structure that enabled discrimination between target mutations that were indistinguishable from steady-state measurements.…”
Section: The Fluorescence Decay Of 2ap In Dna As a Reporter Of Conformentioning
confidence: 99%
See 1 more Smart Citation
“…use the fluorescence decay of 2AP positioned at the branchpoint to probe the conformation (switch state) and to detect structural differences arising from hybridization of matched and mis-matched targets (Campbell et al . 2009). The decay parameters reported enhanced base-stacking at the branchpoint on switch closure and could resolve variations in switch structure that enabled discrimination between target mutations that were indistinguishable from steady-state measurements.…”
Section: The Fluorescence Decay Of 2ap In Dna As a Reporter Of Conformentioning
confidence: 99%
“…There was good agreement between the quantum yields derived from the ultrafast decay parameters and those from the fluorescence intensities, showing that there remained no undetected decay processes faster than the 0.3-ps time resolution of the measurements. In further agreement with the observations of Mély and coworkers,(Avilov et al, 2008), the sub-5 ps decay components were found to be entirely suppressed in the presence of 70% glycerol.To assist in the development of a Holliday junction-based nanoswitch for detection of single-nucleotide mismatches in unlabelled targets, Campbell et al use the fluorescence decay of 2AP positioned at the branchpoint to probe the conformation (switch state) and to detect structural differences arising from hybridisation of matched and mis-matched targets(Campbell et al, 2009). The decay parameters reported enhanced base-stacking at the branchpoint on switch closure and could resolve variations in switch structure that enabled discrimination between target mutations that were indistinguishable from steady-state measurements.We used 2AP time-resolved fluorescence was used to complement single-molecule, multi-parameter Förster resonance energy transfer (FRET) measurements to investigate branchpoint expansion in a three-way junction(Sabir et al, 2012).…”
mentioning
confidence: 99%
“…71,72 Jones and co-workers used 2-aminopurine to investigate base-flipping in M.Hha1-DNA complexes (Fig. 5).…”
Section: Fluorescence-lifetime-based Biosensingmentioning
confidence: 99%
“…Fluorescent base analogs have little influence on the structure of host nucleic acids, but they show sensitive response to the change of the structures, which is well suited for investigating the structure changes of nucleic acids, especially when the change involves protein recognition. 71,72 Jones and co-workers used 2-aminopurine to investigate base-flipping in M.Hha1-DNA complexes (Fig. 5).…”
Section: Fluorescence-lifetime-based Biosensingmentioning
confidence: 99%